The Criminal Liability of An Online Loan For Spreading Personal Private Data - Adjietama Ryan Wichaksono; Rehnalemkan Ginting (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The abuse of personal data in the online loans has been a center of attention in the context of criminal law. This article analyzed the criminal liability of the illegal disclosing personal data in the scheme of online loans. By considering the constitutional law in Indonesia and the recent development of in those fields, this research explored the constitutional implication to the abuse of personal private data by online loans. The research methodology covered the analysis of relevant constitutional laws, court judgment, constitutional literatures, and recent cases. The results showed that the criminal liability can be applied to the online loans which used or spread illegally the private data of a debtor. The misuse of personal data included the illegal disclosing, the violation of privacy, and personal data hijacking. The implementation of constitutional law played an important role in protecting the security and privacy rights of individual data. However, the challenge in implementing the laws was the limited relevant regulation and lack of competent investigator in revealing the illegal activity. This article suggested to increase the effective constitutional frames and law enforcement in handling the problem. The collaboration of government, inspectorate agency, and industry, was considered necessary to make sure that there would be a legal and ethical online loan and the rule-breaking activity could be judged constitutionally